Faith-Based Cooperation in Global Crises: Interreligious Solidarity and Community Resilience - Abdul Aziz Shamhuna (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2025)
This study examines how faith-based communities engage in interreligious cooperation during global crises and how such collaboration strengthens community resilience. Using a qualitative approach, the research draws upon case studies, interviews, and surveys involving religious leaders and participants in interfaith initiatives. The analysis highlights that trust, shared moral values, and coordinated collective action function as the primary drivers of successful interreligious engagement. The findings show that these partnerships frequently emerge during urgent humanitarian and healthcare emergencies, where joint efforts improve access to resources and enhance community-level coping strategies. Moreover, interreligious cooperation contributes not only to mitigating crisis impacts but also to promoting a more holistic approach to public welfare. The study underscores that integrating interfaith strategies into crisis management frameworks can reinforce social cohesion, strengthen mutual understanding, and support long-term community development. Overall, this research contributes to the growing academic discourse on interreligious engagement by demonstrating its significance in addressing contemporary global challenges and by emphasizing the need for further exploration of how faith-based dynamics shape social welfare and resilience.